"I am NN": A Reconstruction of Anscombe's "The First Person". (12th April 2019) - Haddock, Adrian
Abstract: This paper develops a way of understanding G. E. M. Anscombe's essay "The First Person" at the heart of which are the following two ideas: first, that the point of her essay is to show that it is not possible for anyone to understand what they express with "I" as an Art des Gegebenseins —a way of thinking of an object that constitutes identifying knowledge of which object is being thought of; and second, that the argument through which her essay seeks to show this is itself first personal in character. Understanding Anscombe's essay in this light has the merit of showing much of what it says to be correct. But it sets us the task of saying what it is that we understand ourselves to express with "I" if not an Art des Gegebenseins, and in particular what it is that we understand ourselves to express with sentences with "I" as subject that might seem to express identity judgments, such as "I am NN ", and "I am this body".